2014
DOI: 10.4103/0253-7176.130989
|View full text |Cite
|
Sign up to set email alerts
|

Domestic Violence as a Risk Factor for Maternal Depression and Neonatal Outcomes: A Hospital-Based Cohort Study

Abstract: Objectives:This study attempted to follow up a cohort of women who presented to a tertiary hospital to investigate the effect of domestic violence on maternal and neonatal outcomes.Materials and Methods:Women, between 26-34 weeks of gestation, attending the obstetrics outpatient department, were recruited and followed up until delivery. They were assessed at recruitment and after delivery using the Edinburgh Postnatal Depression Scale, the Abuse Assessment Screen, and a pro forma to assess socio-demographic an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
25
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 16 publications
5
25
0
Order By: Relevance
“…Six of these 13 utilised the NFHS-2 and four-year follow-up data from the rural regions of four states to evaluate the effect of DV on mental health disorders (Shidhaye & Patel, 2010), a woman’s adoption of contraception, occurrence of unwanted pregnancy (Stephenson et al, 2008), uptake of prenatal care (Koski et al, 2011), early childhood mortality (Koenig et al, 2010), functional autonomy and reproduction (Bourey, Stephenson, & Hindin, 2013), and contraceptive adoption (Stephenson, Jadhav, & Hindin, 2013), while one used the data to evaluate the effect of autonomy on experience of physical violence (Nongrum, Thomas, Lionel, & Jacob, 2014; Sabarwal, Santhya, & Jejeebhoy, 2014). Only one study employed a case-control study to evaluate the link between DV and child mortality (Varghese, Prasad, & Jacob, 2013) and another utilised a randomised control design to evaluate the effect of a mixed individual and group women’s behavioural intervention in reducing DV and marital conflict over time (Saggurti et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Six of these 13 utilised the NFHS-2 and four-year follow-up data from the rural regions of four states to evaluate the effect of DV on mental health disorders (Shidhaye & Patel, 2010), a woman’s adoption of contraception, occurrence of unwanted pregnancy (Stephenson et al, 2008), uptake of prenatal care (Koski et al, 2011), early childhood mortality (Koenig et al, 2010), functional autonomy and reproduction (Bourey, Stephenson, & Hindin, 2013), and contraceptive adoption (Stephenson, Jadhav, & Hindin, 2013), while one used the data to evaluate the effect of autonomy on experience of physical violence (Nongrum, Thomas, Lionel, & Jacob, 2014; Sabarwal, Santhya, & Jejeebhoy, 2014). Only one study employed a case-control study to evaluate the link between DV and child mortality (Varghese, Prasad, & Jacob, 2013) and another utilised a randomised control design to evaluate the effect of a mixed individual and group women’s behavioural intervention in reducing DV and marital conflict over time (Saggurti et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Only one study employed a case-control study to evaluate the link between DV and child mortality (Varghese, Prasad, & Jacob, 2013) and another utilised a randomised control design to evaluate the effect of a mixed individual and group women’s behavioural intervention in reducing DV and marital conflict over time (Saggurti et al, 2014). The remainder of prospective studies evaluated the causal association between DV and incident STIs and/or attempted suicide (Chowdhary & Patel, 2008; Maselko & Patel, 2008; Weiss et al, 2008), DV and maternal and neonatal health outcomes (Nongrum et al, 2014), the effect of the type of interviewing (face-to-face versus audio computer-assisted self-interviews) on DV reporting (Rathod, Minnis, Subbiah, & Krishnan, 2011), trends in DV occurrence over time (Simister & Mehta, 2010), and the effect of change in a woman or her spouse’s employment status on her experience of DV (Krishnan et al, 2010). …”
Section: Resultsmentioning
confidence: 99%
“…Such acts of domestic violence (DV) have been linked to substantial mental and physical morbidity [ 2 20 ]. Indian women who report DV have a higher likelihood of having depression, post traumatic stress disorder, attempted suicide, and adopting maladaptive health behaviors [ 2 6 , 15 ]. They also report higher frequencies of injuries[ 16 ], chronic diseases such as asthma and anemia, gynecologic morbidity[ 18 , 19 ], and infectious diseases such as sexually transmitted infections and HIV [ 7 10 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…New risk factors for PTB, such as experience of racial discrimination, stress during pregnancy, domestic violence against women, lack of social support, maternal infections (bacterial vaginosis, infections of the oral cavity and urinary tract infections) genetic susceptibility (polymorphisms in the coding of TNF-α and CRH), and medical interventions will be evaluated under the present protocol [ 12 , 13 , 17 , 20 , 25 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted in India detected a 2.59 times higher risk of perinatal and neonatal mortality for the babies of women who are victims of domestic violence [ 19 ]. Nogrum et al [ 20 ] demonstrated that domestic violence was associated with prenatal and postnatal depression, complications of pregnancy, PTB and low birth weight. Despite the magnitude of the problem, few studies have been devoted to the investigation of the association between domestic and family violence against women and PTB.…”
Section: Introductionmentioning
confidence: 99%